The Influence of Organizational Culture on Performance through Employee Work Motivation - Wijayanti, Anna Isnaini; Hernawati, Sri; Puspitaningtyas, Zarah (Health Notions, 2018)
Public health centre is a the technical implementation unit of the office regency are responsible for organizing health development in a working area. In the work environment, Puskesmas is increasingly aware of the importance of organizational culture in working for employees, in order to increase employee work motivation, which will encourage employees to improve their performance. But sometimes the implementation of good performance can not run optimally with existing theory as happened at some health centers in Lumajang district. This research aims was to analyzed the influence of organizational culture on performance through employee worked  motivation in the Worked Areas of  Labruk Kidul Public Health centre, Gesang Public Health centre, and Sukodono Lumajang Public Health Center. This type of research was a observational analytic, and used cross sectional approach method. Sample in this study amounted to 167 employees used total sampling technique, 55 employees in Labruk Kidul Health Center, 53 employees at Gesang Public Health Center, and 59 at Sukodono Lumajang Public Health Center. Data analysis technique was done by Partial Least Square (PLS) method. Based on the test results there was an influence of organizational culture on performance through employee worked motivation, with a t value of 8,716 statistics (t statistics> t table 1.96) means that the better organizational culture applied will increased employee worked motivation, so employee performance will also increased. To realize the excellent service oriented on improving the performance of employees, must be supported from all aspects of human resources, infrastructure, methods, environment both internal and external, and good management, so that existing facilities are expected to facilitate all aspects in the field of health in relation to public services which may h ave an impact on improving the performance of technical officers.